The marriage bargain - Probst, Jennifer (Probst, Jennifer. Marriage to a billionaire series, 2012)
"To save her family home, impulsive bookstore owner, Alexa Maria McKenzie, casts a love spell. But she never planned on conjuring up her best friend's older brother--the powerful man who once shattered her heart. Billionaire Nicholas Ryan doesn't believe in marriage, but in order to inherit his father's corporation, he needs a wife and needs one fast. When he discovers his sister's childhood friend is in dire financial straits, he offers Alexa a bold proposition. A marriage in name only with certain rules: avoid entanglement; keep things all business; do not fall in love. The arrangement is only for a year so the rules shouldn't be that hard to follow, right? Except fate has a way of upsetting the best-laid plans"--P. [4] of cover.